2019
DOI: 10.1155/2019/4727868
|View full text |Cite
|
Sign up to set email alerts
|

Price Linkage Rumors in the Stock Market and Investor Risk Contagion on Bilayer‐Coupled Networks

Abstract: Investor heterogeneities include investor risk preference, investor risk cognitive level, information value, and investor influence. From the perspective of the stock price linkage, this article constructs an SCIR contagion model of investor risk on a single-layer network. It digs out the investor risk caused by rumors in the stock market under the stock price linkage and its contagion mechanism. The function and influence of different mechanism probabilities and investor heterogeneities on the effects of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…In [18], the authors proposed a bilayer network model to investigate the interaction mechanism between information spread and credit risk contagion. In [19], based on the epidemic spread of price linkage rumors, the authors explored the contagion of investor risk and discovered global and local effect of investor heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [18], the authors proposed a bilayer network model to investigate the interaction mechanism between information spread and credit risk contagion. In [19], based on the epidemic spread of price linkage rumors, the authors explored the contagion of investor risk and discovered global and local effect of investor heterogeneity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this relation loses its significance when the sentiment is high. Dong et al discussed the effects of different mechanism probabilities and investor heterogeneity on the risk contagion effect of the stock market [26]. Wang examined the role of institutional investor sentiment in determining betareturn relationships, and through empirical analysis showed that the beta-return relationship is asymmetric between the bearish period and the bullish period [27].…”
Section: Introductionmentioning
confidence: 99%
“…is case in turn will not only amplify the initial impact of the enterprise but also bring deterioration in the financial situation. From the perspective of stock price fluctuation, Dong et al [48] constructed a single-layer network SCIR investor risk contagion model considering the heterogeneity of investors based on the single-layer network SCIR investor risk contagion model. ey constructed a two-layer coupling network investor risk contagion model and compared the evolution characteristics Complexity and rules of investor risk contagion under different connection modes and mechanism probabilities.…”
Section: Introductionmentioning
confidence: 99%